Visão de um jornalista norte-americano na imprensa brasileira : Drew Pearson na Revista O Cruzeiro (1959-1961) - Guarezi, Vagner Paulo Cazarotto (2014)
This study aims to analyze the Carrossel do Mundo colun, written by American journalist Drew Pearson, in the magazine O Cruzeiro in the period 1959-1961. In this analysis, we will highlight the main topics discussed by Pearson. The twentieth century was marked by constant and big evolutions. Many of them have created and fueled the biggest conflicts in history. Ideologies, concepts and new sociological options have emerged, gave options and became references. The technologies developed made life easier, brought borders down and created disputes. The Brazil of this century was designed by American traits. The influence of the United States created concepts and spread the culture, the economy and the ideology in the country. Journalistically speaking, was the American journalism that served as the basis for diagramming and structuring developments in the country. Based on this assumption, the magazine O Cruzeiro, created in 1928, annexed to its gold squadron the American journalist Drew Pearson, reference on the platforms of international politics. In Brazil, O Cruzeiro presented and brought new to the readers. Its circulation allowed to reach the most diverse corners of the country, making their coverage and access become a mark within the study period. Pearson completed the Americanization in the magazine. Divided the pages with of the weekly magazine advertisements, and news about the American imagination. Divided the weekly magazine‟s pages with advertisements and news about the American imagination. Having as object of study the Carrossel do Mundo column, our aim is to show and analyze the topics discussed in the column, immersing ourselves in the international context. The magazine was a vehicle for forming opinion, its contents had a great variety and was focused on a readership of higher purchasing power. The periodic brought news from the perspective of an American journalist, linked to a communication medium with capitalist origins and American ideologies